Multi‐Omic Assessment of Microbial Communities and Their Polyketide Biosynthetic Potential Across Abyssal Sediments - Hans W. Singh; Johanna Gutleben; Alexander Bogdanov; Alexander B. Chase; Alyssa Demko; Sheila Podell; Brian Haley; Paul R. Jensen (Environmental Microbiology, 2026)
Microbially‐derived polyketides include some of today's most valuable medicines, yet their discovery has focused on a narrow subset of Earth's microbial biodiversity. Although understudied biomes such as marine sediments have been targeted, these efforts have focused on samples collected from shallow waters. In contrast, abyssal marine sediments (4000–6000 m), which comprise > 80% of the ocean floor, remain poorly explored. This leaves foundational gaps in our understanding of deep‐sea microbial diversity and its relationship to biosynthetic potential. Here, we used culture‐independent approaches to characterise microbial taxonomic and biosynthetic diversity in abyssal sediments collected from three geochemically distinct plains along an 880 km transect. Sediment communities varied in both taxonomic (16S rRNA gene) and biosynthetic (ketosynthase domain) composition across sites and relative to nearshore sediments, suggesting they harbour unique opportunities for natural product discovery. Ketosynthase phylogenies revealed abyssal clades that diverged from experimentally characterised polyketide synthase pathways, further supporting biosynthetic novelty. Metagenome‐assembled genomes linked unique ketosynthase domains to the poorly studied phylum Gemmatimonadota. Sediment metabolomes provided evidence of chemical novelty, with

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Examination of sex differences in fatigability, muscle oxygenation, and neuromuscular responses during low-intensity isometric handgrip exercise - Minyoung Kwak; Brian Benitez; Pasquale J. Succi; Clara J. Mitchinson; Erik R. Snell; Haley C. Bergstrom (European Journal of Applied Physiology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The behaviour of Ni and its isotopes during early diagenesis of Mn oxide-rich abyssal sediments - Sarah Fleischmann; Jianghui Du; Brian Haley; James McManus; Mingzhao Sun; Derek Vance (Geochimica et Cosmochimica Acta, 2026)

A surface complexation model for simulating sorption of rare earth elements onto goethite in low ionic strength (I = 0.01 M) aqueous solutions for use in groundwater flow systems - Jaxon Dii Horne; Larissa P. Costa; Brian Haley; Karen H. Johannesson (Chemical Geology, 2026)

Decoupling cerium isotope fractionation from cerium anomalies in marine sediments - Wenshuai Li; Ryoichi Nakada; James McManus; Brian A. Haley; Mohsen Shakouri; Fulai Li; Yoshio Takahashi (Earth and Planetary Science Letters, 2025)

Intact core mesocosms demonstrate effects of temperature and salinity on nitrogen cycling and microbial community structure under pulse and press disturbances - Brian R. Donnelly; Haley Nickel; Jennifer L. Bowen (Limnology and Oceanography, 2025)
Tidal freshwater wetlands are critical for removing or sequestering watershed‐derived nitrogen loads before they reach the coast, where they can lead to eutrophication. However, rising seas and increasing climate variability will alter important physicochemical parameters that control nitrogen generation (e.g., nitrogen fixation) and removal processes (e.g., denitrification) in these habitats. Furthermore, the frequency and timing of these changes could vary from short, finite pulses during a storm or drought to long‐term presses from sea level rise, which may differentially affect biogeochemical cycling. We used intact core mesocosms to examine how microbial community structure and nitrogen cycling changed in response to increased temperature and salinity under pulse and press disturbances. We found that net N 2 flux rates, defined as the balance between nitrogen fixation, which adds nitrogen, and denitrification, which removes it, did not directionally change in response to stressor pulse or press. Instead, it became more variable under both disturbance regimes, underscoring the importance of both denitrification and nitrogen fixation in these systems. Nitrous oxide production rates, however, decreased and became more stable over time in the press scenario but remained highly variable in the pulse scenario. Under both pulse and press disturbance, both the overall and the active component of the microbial community changed, particularly in response to the salinity treatment. Although there was an overall community shift, core members of the microbiome capable of denitrification and nitrogen fixation persisted. Both pulses and presses of temperature and salinity changed the microbial communities of tidal freshwater wetlands, but a combination of microbial resistance and functional redundancy appears to allow important N cycling processes to persist. These findings provide valuable knowledge on the functional and structural potential of the nitrogen cycling microbial communities in tidal freshwater wetlands when facing future climate variability.

Understanding the phase associations and weathering behavior of rhenium to assess the use of Re as a tracer of georespiration - Layla Ghazi; Miguel Goñi; Brian Haley; Jesse M. Muratli; Julie C. Pett-Ridge (Chemical Geology, 2025)

Influence of deception of task duration on the sex-specific physiological responses to RPE-clamp cycle ergometry - Pasquale J. Succi; Brian Benitez; Minyoung Kwak; Clara J. Mitchinson; Timothy A. Butterfield; Michael A. Samaan; Jody L. Clasey; Haley C. Bergstrom (European Journal of Applied Physiology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Vigorous intensity heart rate-clamp exercise does not elicit recommended oxygen consumption rates - Clara J. Mitchinson; Djadmann Gustave; Pasquale J. Succi; Brian Benitez; Minyoung Kwak; Haley C. Bergstrom (European Journal of Applied Physiology, 2025)

The effects of low vs. high rating of perceived exertion clamp exercise on performance, neuromuscular, and muscle oxygen saturation responses in females - Minyoung Kwak; Pasquale J. Succi; Brian Benitez; Clara J. Mitchinson; Haley C. Bergstrom (European Journal of Applied Physiology, 2025)

Evaluation of preoperative intraperitoneal injection of bupivacaine for intraoperative antinociception in cats undergoing ovariohysterectomy: A randomized clinical trial - Brandon M. Lawler; Alonso G.P. Guedes; Caitlin C. Tearney; Lauren Ienello; Brian Walters; Adrienne L. Haley; Erin Wendt-Hornickle (Research in Veterinary Science, 2024)

No sex differences in time-to-task failure and neuromuscular patterns of response during submaximal, bilateral, isometric leg extensions - Brian Benitez; Minyoung Kwak; Pasquale J. Succi; Clara Mitchinson; Haley C. Bergstrom (European Journal of Applied Physiology, 2024)

The Rb isotope composition of modern seawater and outputs to deep-sea sediments - Xingchao Zhang; Limei Tang; Jianghui Du; Brian A. Haley; James McManus; Xia Hu; Fang Huang (Earth and Planetary Science Letters, 2024)

Suspended particulate matter influence on dissolved Nd concentration and isotopic composition along GEOTRACES section GP16 - Chandranath Basak; Yingzhe Wu; Brian A. Haley; Jesse Muratli; Leopoldo D. Pena; Louise Bolge; Jessica N. Fitzsimmons; Robert M. Sherrell; Steven L. Goldstein (Earth and Planetary Science Letters, 2024)

Sustainability and perceptual responses during handgrip holds to failure at two fatigue thresholds - Minyoung Kwak; Pasquale J. Succi; Brian Benitez; Haley C. Bergstrom (European Journal of Applied Physiology, 2023)

Electromyographic and mechanomyographic responses of the biceps brachii during concentric and eccentric muscle actions to failure at high and low relative loads - Brian Benitez; Taylor K. Dinyer-McNeely; Lindsay McCallum; Minyoung Kwak; Pasquale J. Succi; Haley C. Bergstrom (European Journal of Applied Physiology, 2023)

Recognizing flood exposure inequities across flood frequencies - Haley Selsor; Brian P. Bledsoe; Roderick Lammers (Anthropocene, 2023)

Methodological considerations for the determination of VO2max in healthy men - Pasquale J. Succi; Brian Benitez; Minyoung Kwak; Haley C. Bergstrom (European Journal of Applied Physiology, 2023)

Cyanidin improves oocyte maturation and the in vitro production of pig embryos - Emma Hicks; Miranda Mentler; Haley A. Arena; Jaelyn Z. Current; Brian D. Whitaker (In Vitro Cellular & Developmental Biology - Animal, 2020)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The Impact of Benthic Processes on Rare Earth Element and Neodymium Isotope Distributions in the Oceans - Brian A. Haley; Jianghui Du; April N. Abbott; James McManus (Frontiers in Marine Science, 2017)

Rare earth element geochemistry in cold-seep pore waters of Hydrate Ridge, northeast Pacific Ocean - Tobias Himmler; Brian A. Haley; Marta E. Torres; Gary P. Klinkhammer; Gerhard Bohrmann; Jörn Peckmann (Geo-Marine Letters, 2013)

Regional administration of oncolytic Echovirus 1 as a novel therapy for the peritoneal dissemination of gastric cancer - Erin S. Haley; Gough G. Au; Brian R. Carlton; Richard D. Barry; Darren R. Shafren (Journal of Molecular Medicine, 2009)